Being a Naturalist Guide in Bardiya, Nepal: Evolution and Retrospective Analysis - Vouiller, Nolwen (Far Western Review, 2023)
This article, dealing with the profession of guiding in Bardiya National Park, is based on a previous paper (Vouiller, 2022) recently published in Studies in Nepali History and Society (SINHAS, Kathmandu), highlighting data gathered in 2019 with that of 2021-2022. While I presented the guide profession as being a clever adaptation to modernity, as an ‘in-between’, I would like here to accentuate the role of social networks, the process of ‘’heroisation’’ that takes place, but also the importance of the senses and the reading of signs in the practice of the profession. Bardiya National Park, established between 1988 and 1989, hosts very little anthropological work, it is more the object of research from developmental or natural sciences. The PhD I am currently pursuing in social and political sciences in Belgium (ULiège) and France (EHESS), is based on more than one year of fieldwork in Bardiya. It aims to understand how humans adapt psycho-corporeally and socially to the proximity of the Park’s animals. I am working with participant observation, semi-directive interviews with the professions most in contact with the animals of the Park, direct and indirect observations of encounters and finally linguistic analysis of the terms used in the discourses and on social media. The guiding subject in Bardiya is complex and representative of very topical internal and political tensions. Based on part of my doctoral work, I hope to show some of the factors that I believe will determine the future of tourism and human-animal cohabitation in Bardiya.